â€œNur Muhammadâ€ dalam Naskah Klasik Gorontalo - Sofyan A. P. Kau (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
â€œNur Muhammadâ€ is a popular concept in the discourse of Sufism falsafati. In Gorontalo, texts of Muhammad Nur iw widely known. The texts, as the author of the findings gathered in a collection of manuscripts under the theme